An auxin signaling network translates low-sugar-state input into compensated cell enlargement in the fugu5 cotyledon. - Hiromitsu Tabeta; Shunsuke Watanabe; Keita Fukuda; Shizuka Gunji; Mariko Asaoka; Masami Yokota Hirai; Mitsunori Seo; Hirokazu Tsukaya; Ali Ferjani (PLoS Genetics, 2021)
In plants, the effective mobilization of seed nutrient reserves is crucial during germination and for seedling establishment. The Arabidopsis H+-PPase-loss-of-function fugu5 mutants exhibit a reduced number of cells in the cotyledons. This leads to enhanced post-mitotic cell expansion, also known as compensated cell enlargement (CCE). While decreased cell numbers have been ascribed to reduced gluconeogenesis from triacylglycerol, the molecular mechanisms underlying CCE remain ill-known. Given the role of indole 3-butyric acid (IBA) in cotyledon development, and because CCE in fugu5 is specifically and completely cancelled by ech2, which shows defective IBA-to-indoleacetic acid (IAA) conversion, IBA has emerged as a potential regulator of CCE. Here, to further illuminate the regulatory role of IBA in CCE, we used a series of high-order mutants that harbored a specific defect in IBA-to-IAA conversion, IBA efflux, IAA signaling, or vacuolar type H+-ATPase (V-ATPase) activity and analyzed the genetic interaction with fugu5-1. We found that while CCE in fugu5 was promoted by IBA, defects in IBA-to-IAA conversion, IAA response, or the V-ATPase activity alone cancelled CCE. Consistently, endogenous IAA in fugu5 reached a level 2.2-fold higher than the WT in 1-week-old seedlings. Finally, the above findings were validated in icl-2, mls-2, pck1-2 and ibr10 mutants, in which CCE was triggered by low sugar contents. This provides a scenario in which following seed germination, the low-sugar-state triggers IAA synthesis, leading to CCE through the activation of the V-ATPase. These findings illustrate how fine-tuning cell and organ size regulation depend on interplays between metabolism and IAA levels in plants.